The complete chloroplast genome sequence of Panax quinquefolius (L.). (3rd July 2016) - Kim, Kyunghee; Lee, Sang-Choon; Lee, Junki; Kim, Nam-Hoon; Jang, Woojong; Yang, Tae-Jin
Abstract: The complete chloroplast genome sequence of Panax quinquefolius, an important medicinal herb, was generated by de novo assembly with low-coverage whole-genome sequence data and manual correction. A circular 156 088-bp chloroplast genome showed typical chloroplast genome structure comprising a large single copy region of 86 095 bp, a small single copy region of 17 993 bp, and a pair of inverted repeats of 26 000 bp. The chloroplast genome had 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis with the chloroplast genome revealed that P. quinquefolius is much closer to P. ginseng than P. notoginseng .